2019
DOI: 10.1016/j.cognition.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolving artificial sign languages in the lab: From improvised gesture to systematic sign

Abstract: Recent work on emerging sign languages provides evidence for how key properties of linguistic systems are created. Here we use laboratory experiments to investigate the contribution of two specific mechanismsinteraction and transmission-to the emergence of a manual communication system in silent gesturers. We show that the combined effects of these mechanisms, rather than either alone, lead to a gradual increase of regularity, systematic structure and communicative efficiency. The gestures initially produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 53 publications
6
105
1
Order By: Relevance
“…In our study, gesturers, who lack a conventionalised manual lexicon, are also capable of making subtle semantic distinctions through the combination of gestures with different iconic modes of representation. Critically, this level of combinatorial patterning is in place at the first instance of spontaneous gestural production and without repeated iterations of cultural transmission, as has been reported in other studies (Micklos, 2016; Motamedi, Schouwstra, Culbertson, Smith, & Kirby, 2018).
Fig.
…”
Section: Discussionsupporting
confidence: 68%
“…In our study, gesturers, who lack a conventionalised manual lexicon, are also capable of making subtle semantic distinctions through the combination of gestures with different iconic modes of representation. Critically, this level of combinatorial patterning is in place at the first instance of spontaneous gestural production and without repeated iterations of cultural transmission, as has been reported in other studies (Micklos, 2016; Motamedi, Schouwstra, Culbertson, Smith, & Kirby, 2018).
Fig.
…”
Section: Discussionsupporting
confidence: 68%
“…Finally, there is one study we are aware of that combines improvisation, communicative interaction, and transmission to new learners, bringing together all three processes reviewed above. Motamedi et al (2019) focused on how participants use improvised silent gesture to communicate about sets of thematically related concepts (e.g. chef, frying pan; hairdresser, scissors), and how their gestures develop over time in interaction between pairs of participants and/or across generations of learners.…”
Section: Iterationmentioning
confidence: 99%
“…The study directly compared a communication condition, in which participants communicate repeatedly about the same concepts using initially improvised gestures, to an iterated condition, in which the output of one communicating pair is transmitted to a new pair of participants, for multiple generations (following the setup in Kirby et al (2015), but with an improvised gesture starting-point). Motamedi et al (2019) showed that systematic functional markers (gestures that indicate the meaning class a concept belongs to, such as a 'point-to-self' gesture to denote a person for a concept like 'chef') are rare in improvised gesture, emerge to some extent in the communication condition, but become prevalent and systematic when communicative interaction was combined with iterated transmission to new generations of learners.…”
Section: Iterationmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the term 'artificial sign language' we do not intend to suggest that the necessarily simplified system of gestures we test in our experiment are comparable to the full complexity of natural signed languages. Instead, we use the term to indicate that our methodology is an extension of artificial language learning paradigms (see Motamedi, Schouwstra, Smith, Culbertson, & Kirby, 2019). That is, our stimuli represent a necessarily simplified system, aiming to isolate the particular properties we are interested in, and we hope that the result is language-like in relevant and informative ways.…”
Section: Introductionmentioning
confidence: 99%